DLK2 regulates arbuscule hyphal branching during arbuscular mycorrhizal symbiosis. Issue 1 (20th October 2020) - Ho‐Plágaro, Tania; Morcillo, Rafael J. L.; Tamayo‐Navarrete, María Isabel; Huertas, Raúl; Molinero‐Rosales, Nuria; López‐Ráez, Juan Antonio; Macho, Alberto P.; García‐Garrido, José Manuel
Summary: D14 and KAI2 receptors enable plants to distinguish between strigolactones (SLs) and karrikins (KARs), respectively, in order to trigger appropriate environmental and developmental responses. Both receptors are related to the regulation of arbuscular mycorrhiza (AM) formation and are members of the RsbQ‐like family of α, β‐hydrolases. DLK2 proteins, whose function remains unknown, constitute a third clade from the RsbQ‐like protein family. We investigated whether the tomato SlDLK2 is a new regulatory component in the AM symbiosis. Genetic approaches were conducted to analyze SlDLK2 expression and to understand SlDLK2 function in AM symbiosis. We show that SlDLK2 expression in roots is AM‐dependent and is associated with cells containing arbuscules. SlDLK2 ectopic expression arrests arbuscule branching and downregulates AM‐responsive genes, even in the absence of symbiosis; while the opposite effect was observed upon SlDLK2 silencing. Moreover, SlDLK2 overexpression in Medicago truncatula roots showed the same altered phenotype observed in tomato roots. Interestingly, SlDLK2 interacts with DELLA, a protein that regulates arbuscule formation/degradation in AM roots. We propose that SlDLK2 is a new component of the complex plant‐mediated mechanism regulating the life cycle of arbuscules in AM symbiosis.